Using Techniques and Introductory Activities Productively in Teaching Foreign Languages - Kipchakova Sanobar (International Journal on Integrated Education, 2022)
This article discusses some of the problems and shortcomings in the educational process. The advantages of using high technology in improving the quality of education and teaching students are highlighted.